Electron-beam irradiation preserves nutritional profile of Agaricus bisporus Portobello - Cardoso, Rossana V.C. (2018)
All over the world, mushrooms are highly consumed due to their high contents of digestible proteins, carbohydrates, vitamins and fibers. Mushrooms contain about 90% of water, which leads to a faster deterioration due to senescence, browning, water loss and microbial attack. Despite of the immense popularity of this food worldwide, data regarding alternative technologies to increase mushrooms shelf-life are scarce. Ionizing radiation processing is recognized as a safe and effective method for conservation, being widely used to extend the shelf-life of raw foods. The present work reports the effects of storage time (0, 4 and 8 days) and electron-beam irradiation on the nutritional composition (moisture, fat, proteins, ash, carbohydrates and energy) of Agaricus bisporus Portobello samples. The irradiation was performed with a 10 MeV energy irradiator at the doses of 1, 2 and 5 kGy. The proximate composition was evaluated by AOAC official procedures. Storage time (ST) and electron-beam (EB) irradiation showed a significant interaction in all cases (p-value > 0.05), indicating that the effects potentially exerted by ST depended on EB dose and vice-versa. Considering the individual effect of each factor, EB induced more changes than ST, which in fact had a significant effect only for protein and carbohydrates. Among different EB doses, despite the significant differences, it is evident that the nutritional profiles were not greatly changed with any applied dose. Therefore, up to 5 kGy, EB seems to be a suitable conservation treatment for A. bisporus Portobello.